2014
DOI: 10.1002/zaac.201400378
|View full text |Cite
|
Sign up to set email alerts
|

Late Metal Scaffolds that Activate Both, Dinitrogen and Reduced Dinitrogen Species NxHy

Abstract: Abstract. In the context of biological nitrogen fixation, the question whether molybdenum or iron is the site for substrate binding and reduction is still discussed controversially. Therefore, the development of relevant model compounds containing early or late transition metals is essential in understanding the nature and behavior of intermediates bound to the FeMo-cofactor. Ligated early transition metal atoms are known to strongly activate N 2 and mediate its cleavage, but the resulting complexes contain me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 173 publications
0
31
1
Order By: Relevance
“…61,157,191,192,41,44,165 Peters has shown that phosphine ligands provide excellent platforms for functionalization of N 2 on iron, 60,193,194 and enable characterization of potential N 2 reduction intermediates Fe-N x H y , 98,99,165,194196 including systems that feature a coordinated hydride. 40,42,43 Ammonia production by tripodal trisphosphine ligands with an axial donor (Si, C, or B) increases in the order Si < C < B. 165 The higher degree of Fe-heteroatom bond flexibility in 42 could be crucial for stabilizing the variety of N 2 reduction intermediates in the catalytic cycle.…”
Section: Fe-nxhy Complexes With Sulfur Ligandsmentioning
confidence: 99%
“…61,157,191,192,41,44,165 Peters has shown that phosphine ligands provide excellent platforms for functionalization of N 2 on iron, 60,193,194 and enable characterization of potential N 2 reduction intermediates Fe-N x H y , 98,99,165,194196 including systems that feature a coordinated hydride. 40,42,43 Ammonia production by tripodal trisphosphine ligands with an axial donor (Si, C, or B) increases in the order Si < C < B. 165 The higher degree of Fe-heteroatom bond flexibility in 42 could be crucial for stabilizing the variety of N 2 reduction intermediates in the catalytic cycle.…”
Section: Fe-nxhy Complexes With Sulfur Ligandsmentioning
confidence: 99%
“…[1] To elucidate the reaction mechanism of nitrogen fixation catalyzed by nitrogenases,t he synthesis and reactivity of various transition-metal dinitrogen complexes have been extensively studied. [2,3] As ar esult, nitrogen fixation with molybdenum dinitrogen complexes as the catalysts under ambient reaction conditions was achieved by Schrock and Yandulov in 2003 [4] and by our groups in 2010. [5] Recently,Peters and co-workers developed an iron-catalyzed reduction of molecular dinitrogen into ammonia using iron dinitrogen complexes as catalysts under mild reaction conditions.…”
mentioning
confidence: 94%
“…[6] However,t he transformation of molecular dinitrogen into ammonia under mild reaction conditions using other transition-metal dinitrogen complexes as the catalysts has not yet been achieved. [2,3] Thef irst cobalt dinitrogen complex, [Co(H)(N 2 )(PPh 3 ) 3 ], was reported by Yamamoto and co-workers as the successful example of the synthesis of at ransition-metal dinitrogen complex directly from dinitrogen gas. [7] Since the discovery of this complex, detailed studies on the stoichiometric reactivity of avariety of cobalt dinitrogen complexes have been carried out by several research groups.…”
mentioning
confidence: 99%
“…Efficient catalytic reduction-functionalization of molecular nitrogen (N 2 ) represents an as yet unsolved synthetic challenge inspired by nature [1][2][3][4]. Nitrogen is an essential element for all living systems.…”
Section: Introductionmentioning
confidence: 99%